In situ diffraction study on the annealing performance of a rapidly solidified ribbon consolidated Mg-Ca-Y-Zn-Mn alloy - Jenő Gubicza; Kristián Máthis; Péter Nagy; Péter Jenei; Zoltán Hegedűs; Andrea Farkas; Jozef Veselý; Shin-ichi Inoue; Daria Drozdenko; Yoshihito Kawamura (Journal of Magnesium and Alloys)
Dilute Mg alloys processed by the rapidly solidified ribbon consolidation (RSRC) technique are candidate materials for structural applications due to their enhanced mechanical performance. The thermal stability of the structure in these alloys strongly influences their mechanical performance at elevated temperatures. In this study, an RSRC-processed Mg–1% Ca–0.5% Zn–0.1% Y–0.03% Mn (at%) alloy was heated at a constant rate up to 833 K, and concurrently in situ X-ray diffraction (XRD) measurements were performed using synchrotron radiation in order to monitor the changes in the structure. In addition, ex situ electron microscopy investigations were carried out before and after annealing to complete the XRD study. On the basis of XRD results, the stages of the microstructure evolution during heating were identified. In addition, the thermal expansion coefficients of the matrix and the Mg2Ca secondary phase were determined. Between 299 and 400 K, the lattice constants of both the matrix and the Mg2Ca phase increased due to thermal expansion. In the temperature range of 400-673 K, the increase of the lattice constants with increasing the temperature continued, but their rate was different for the two phases which can induce thermal stresses. Between 673 and 753 K, the lattice constants of the secondary phase did not change most probably due to the compensating effects of the thermal expansion and the decrease of the Ca content. In the temperature range of 753–793 K, the Mg2Ca phase started to dissolve. Between 793 and 833 K the dissolution continued, and additionally the matrix was partially melted.